Effects of carbonate alkalinity on branchial gene expression in the large-scale loach (Paramisgurnus dabryanus) - Huang, Mei; Wu, Meng-Xiao; Zhang, Lin-Jiang; Mi, Di; Zhang, Yun-Long (Frontiers in Marine Science, 2022)
Elucidating the mechanisms of alkaline tolerance in freshwater teleosts will help in the development of commercial saline-alkaline aquaculture. The large-scale loach (Paramisgurnus dabryanus) is a viable species for such aquaculture, but the mechanisms of its tolerance of alkaline water are unclear. Large-scale loach was exposed to 40, 50, and 60 mmol L-1 NaHCO3 for 12, 48, and 96 h to evaluate the transcriptional changes of branchial Rhesus (Rh) glycoproteins, and aquaporins (Aqp)1 and Aqp3. Rhag transcript levels increased with longer exposure times. Rhag expression also rose considerably at higher carbonate alkalinities. Rhbg mRNA levels declined significantly under carbonate alkalinity exposure. A marked up-regulation of Rhcg was observed in the gills of the loach. Exposure to 60 mmol L-1 NaHCO3 also induced a significant up-regulation of aqp1. By contrast, aqp3 expression was significantly lower after 48 h exposure. The current findings reveal that the large-scale loach up-regulates Rhag and Rhcg to enhance ammonia efflux from the gills when exposed to high alkalinity. It is proposed that this species maintains appropriate osmolality when adapting to an alkaline environment by down-regulating aqp3 (to impede urea removal) and up-regulating aqp1 in the gills (to excrete excessive internal water).